Biotechnological applications of mammalian odorant-binding proteins - Gonçalves, Filipa (2021)
The olfactory system of mammals allows the detection and discrimination of thousands of odors from the environment. In mammals, odorant-binding proteins (OBPs) are considered responsible to carry odorant molecules across the aqueous nasal mucus to the olfactory receptors (ORs). The three-dimensional structure of these proteins presents eight antiparallel ?-sheets and a short ?-helical segment close to the C terminus, typical of the lipocalins family. The great ability of OBPs to bind differentiated ligand molecules has driven the research to understand the mechanisms underlying the OBP function in nature and the development of advanced biotechnological applications. This review describes the role of mammalian OBPs in the olfactory perception, highlighting the influence of several key parameters (amino acids, temperature, ionic strength, and pH) in the formation of the OBP/ligand complex. The information from the literature regarding OBP structure, affinity, the strength of binding, and stability inspiring the development of several applications herein detailed.